Father Bear comes home - Minarik, Else Holmelund; Sendak, Maurice (New York : HarperCollins Publishers, 1987)
Collects four stories featuring Little Bear and his adventures with his family, including "Father Bear Comes Home," in which Little Bear hopes that his father returns from his fishing trip with a mermaid.
Little Bear and Owl -- Father Bear comes home -- Hiccups -- Little Bear's mermaid.
School Library Journal, October 2010
Booklist, February 2003
New York Times, July 2006
Horn Book, October 2001
Bulletin (Center for Children's books), January 1996
2.4
Keywords: Bears -- Juvenile fiction; Owls -- Juvenile fiction; Mermaids -- Juvenile fiction; Families -- Juvenile fiction; Bears -- Fiction; Owls -- Fiction; Mermaids -- Fiction; Family life -- Fiction; Bears -- Fiction; Owls -- Fiction; Mermaids and mermen -- Fiction; Family life -- Fiction; Readers (Elementary)